Empreendedorismo de base tecnológica e desenvolvimento regional - Zampieri, Nilza Luiza Venturini (2010)
Is important that the institutions of education and research take the role of educators of entrepreneurs and creators of new businesses, a move that added to its traditional functions expands opportunities for more people being motivated to start their own business. To do this requires a culture change in leaders, teachers, technicians, students, funding agencies, the community finally outside of the whole society. The present study aims at analyzing the contribution of the Technology Incubator of Santa Maria for the entrepreneurial training of students as well as with the formation of innovative companies contributing to the development of Santa Maria and region. The research method was case study, in which the object on which it was applied was the Technology Incubator of Santa Maria (ITSM). Still, the data collection was in two stages: first, to be interviewed experts from different institutions, UFSM, the City of Santa Maria, graduated companies and incubator companies with market expertise. In the second step were applied 33 questionnaires with entrepreneurs incubated in ITSM. The main results highlight the importance of ITSM for the Central Region of Rio Grande do Sul This perception is confirmed both by the actors of the City, as well as by the actors and entrepreneurs UFSM already graduated. A good assessment of ITSM by entrepreneurs and highlight its importance for the maintenance and assistance of incubator companies. Finally, another important point observed by the different actors, is the fact that the vast majority support the deployment of the technology park of Santa Maria.